Luminescence responsive composites of rare earth metal-organic frameworks covalently linking microsphere resin. (February 2020) - Ma, Jing; Zhao, Li-Min; Jin, Chuan-Yu; Yan, Bing
Abstract: In this context, novel luminescence responsive composites are assembled with both rare earth metal-organic framework of 2-aminoterephthalic acid (2 amino-1, 4-benzendicarboxylic acid, NH2 -BDC) and two microsphere-like polymer resins (Wang resin (WR) and Merrifield resin (MR)) through the covalently post-synthetic modification. The final composites MR/WR-MOF-RE (RE = Eu, Tb, Sm) are prepared by the nucleophilic substitution reaction between amino groups of RE-MOF and methyl chloride groups of WR/MR to achieve the chemical linking from each other, whose physical characterization and luminescence responsive property are studied in detail. The composites present the regular microsphere morphology and characteristic photoluminescence of RE 3+ under specific excitation wavelength and the close white color emission can be tuned through adjusting the excitation wavelength for europium hybrid system. Furthermore, MR-MOF-Eu composite is chosen to check the luminescence sensing on volatile solvents, revealing that ammonia vapors and THF can cause apparent luminescence quenching for the different quenching performance. Graphical abstract: Hybrids MR/WR-MOF-RE (RE = Eu, Tb, Sm) are assembled through nucleophilic substitution reaction between amino groups of RE-MOF and methyl chloride groups of WR/MR respectively. They display the characteristic luminescence of RE 3+ and multi-color luminescence can be tuned through adjusting the excitation wavelength. MR-MOF-Eu is select to sense volatile solvents, showing ammonia and THF for luminescence quenching with different performance. Image 1 Highlights: Luminescent responsive hybrids with rare earth MOFs and polymer resin microsphere. The feature luminescence of Eu 3+ /Tb 3+ /Sm 3+ ions for the energy transfer from MOFs. White luminescence tuned by adjusting excitation wavelength. Chemical sensing volatile substances for luminescence quenching of ammonia vapor.